Analysis of the Performance Accountability Evaluation Results of Government Agencies: A Document Study of the AKIP Evaluation Report (LHE AKIP) of the Tualang District Office, Siak Regency, 2022–2024 - Debora, Nora; Sobirin, Muhammad; R.F.S., Harapan Tua (International Journal of Education, Information Technology, and Others, 2025)
The implementation of the Government Agency Performance Accountability System (SAKIP) at the sub-district level presents multidimensional challenges that necessitate a longitudinal analytical approach to identify developmental patterns and systemic constraints. This study examines the SAKIP evaluation outcomes of the Tualang Sub-District Office, Siak Regency, for 2022–2024 by analyzing the AKIP Evaluation Reports (LHE). The results reveal an upward trend in accountability scores—from 66.35 in 2022 to 69.55 in 2024—yet the performance remained confined to the “Good” category without reaching the “Very Good” threshold. Component-based assessment indicates uneven improvement: performance planning and measurement improved by 0.9 and 3.3 points respectively, while performance reporting declined sharply by 4.05 points in 2024. This stagnation underscores the urgency of enhancing institutional capacity, strengthening inter-unit coordination, and optimizing the follow-up of evaluation recommendations. The study contributes theoretically to the discourse on SAKIP effectiveness at the sub-district level and provides practical insights for local governments aiming to strengthen sustainable public sector performance accountability.